2020
DOI: 10.13189/cea.2020.080434
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Stress and Suction Correlation of Compacted, Heaving Soils

Abstract: The behaviour of unsaturated soils is mainly influenced by suction. When unsaturated soils display swelling properties, it becomes fundamental to investigate the impact of soil suction on the swelling stress. A survey was done across Free State province in South Africa and samples were obtained from Bloemfontein, Winburg, and Welkom. Geotechnical studies were performed on particle size definition, free swell ratio, free swell index, Atterberg limits, X-ray diffraction, proctor compaction test, soil suction mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Water molecules are strongly attracted to clay mineral surfaces and can distribute itself evenly throughout the water. The predominant clay mineral which has high swelling stress and soil suction can hold the water together [25]. Furthermore, it is believed that this housing area was a dumping site originally from a small stream before constructing this house.…”
Section: Results Of Resistivity Test and Soil Profilingmentioning
confidence: 99%
“…Water molecules are strongly attracted to clay mineral surfaces and can distribute itself evenly throughout the water. The predominant clay mineral which has high swelling stress and soil suction can hold the water together [25]. Furthermore, it is believed that this housing area was a dumping site originally from a small stream before constructing this house.…”
Section: Results Of Resistivity Test and Soil Profilingmentioning
confidence: 99%
“…The outcome is in line with the studies performed by [20,21] reported the increment of the SS when the dry density increases. Reference [103] investigated the correlation between SS and suction of compacted expansive soils. The outcomes reveal that at W OP , the SS values range from 177kPa to 326kPa.…”
Section: Compactionmentioning
confidence: 99%
“…it was considered desirable to perform multilinear regression analysis based on each of the measured soil properties to predict the dependent variable and validate models with an independent dataset. Regression analysis is applied to assess the relationship between soil properties and swelling stress particularly for expansive soils [38,39]. The experimental data in Table 3 were used to develop the models, due to the influence of FSI, GMC, P.I., and matric suction on swelling stress.…”
Section: Development Of Multi-regression Predictive Models For Swelling Stressmentioning
confidence: 99%